ISLAM DAN KEPEMIMPINAN PEREMPUAN DI RANAH POLITIK - Diana, M.Si, Ilfi Nur (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2008)
Women’s rights are mostly experiencing pressures and obstacles from all sides (groups) which are still influenced by patriarchal culture. In fact, Islam has devoted proportional rights to women such as political right, socio-ecomic rights, educational right as well as cultural right. However, their rights are sometimes socially overlooked for the religious reasons. On the contrary, that phenomenon is generated from the interpretation which is influenced by the interpreter’s conditional and situational background. The most indisputable issue in recent situation is the illegibility of woman being a leader that she cannot be for any political positions. Therefore, it is necessary to do structural transformation and quality and capacity development in the same time. It is also one of effort that we need more humanistic interpretation of the Qur’an toward women.